Estimated population wide benefits and risks in China of lowering sodium through potassium enriched salt substitution: modelling study. (22nd April 2020) - Marklund, Matti; Singh, Gitanjali; Greer, Raquel; Cudhea, Frederick; Matsushita, Kunihiro; Micha, Renata; Brady, Tammy; Zhao, Di; Huang, Liping; Tian, Maoyi; Cobb, Laura; Neal, Bruce; et al.
Abstract: Objectives: To estimate the effects of nationwide replacement of discretionary salt (used at table or during cooking) with potassium enriched salt substitute on morbidity and death from cardiovascular disease in China. Design: Modelling study. Setting: China. Population: Adult population in China, and specifically individuals with chronic kidney disease (about 17 million people). Interventions: Comparative risk assessment models were used to estimate the effects of a nationwide intervention to replace discretionary dietary salt with potassium enriched salt substitutes (20-30% potassium chloride). The models incorporated existing data and corresponding uncertainties from randomised trials, the China National Survey of Chronic Kidney Disease, the Global Burden of Disease Study, and the Chronic Kidney Disease Prognosis Consortium. Main outcome measures: Averted deaths from cardiovascular disease, non-fatal events, and disability adjusted life years from a reduction in blood pressure were estimated after implementation of potassium enriched salt substitution. In individuals with chronic kidney disease, additional deaths from cardiovascular disease related to hyperkalaemia from increased intake of potassium were calculated. The net effects on deaths from cardiovascular disease were estimated as the difference and ratio of averted and additional deaths from cardiovascular disease. Results: Nationwide implementation of potassium enriched salt substitution could prevent about 461 000 (95% uncertainty interval 196 339 to 704 438) deaths annually from cardiovascular disease, corresponding to 11.0% (4.7% to 16.8%) of annual deaths from cardiovascular disease in China; 743 000 (305 803 to 1 273 098) non-fatal cardiovascular events annually; and 7.9 (3.3 to 12.9) million disability adjusted life years related to cardiovascular disease annually. The intervention could potentially produce an estimated 11 000 (6422 to 16 562) additional deaths related to hyperkalaemia in individuals with chronic kidney disease. The net effect would be about 450 000 (183 699 to 697 084) fewer deaths annually from cardiovascular disease in the overall population and 21 000 (1928 to 42 926) fewer deaths in individuals with chronic kidney disease. In deterministic sensitivity analyses, with changes to key model inputs and assumptions, net benefits were consistent in the total population and in individuals with chronic kidney disease, with averted deaths outweighing additional deaths. Conclusions: Nationwide potassium enriched salt substitution in China was estimated to result in a substantial net benefit, preventing around one in nine deaths from cardiovascular disease overall. Taking account of the risks of hyperkalaemia, a substantial net benefit was also estimated for individuals with chronic kidney disease.